A semi-empirical formula for calculating the breaking depth of plunging waves. Issue 2 (3rd April 2019) - Xie, Wenang; Shibayama, Tomoya; Esteban, Miguel
ABSTRACT: A new semi-empirical formula for calculating the breaking depth of plunging breakers is proposed in this study. The shallow water equation is used as the governing equation, and the wave front slope, which is one of the key parameters that governs the breaking criterion, is obtained from it analytically. The analytical formula was then modified based on both physical considerations and historical laboratory data. The accuracy of the resulting semi-empirical formula was examined using two sets of new laboratory data – including laboratory experiments performed by the authors – in order to verify its applicability. The results indicate that the proposed new formula is more accurate than existing formulas.